Disability status and expectations of disability services among individuals with chronic diseases - Gökşen Polat; Funda Sofulu; Gönül Düzgün; Beyzanur Sütçü; Elif Ünsal Avdal (PLoS ONE, 2026)
Background Disability is a multidimensional condition arising from impairment or chronic illness that limits individuals’ ability to perform age, gender, and socio-culturally expected activities. Many chronic diseases, including asthma, diabetes, cardiovascular diseases, cancer, and neurological disorders, fall within the scope of disability. Beyond functional limitations, barriers to social relationships and cultural participation further affect individuals’ lives, underscoring the importance of examining lived experiences and expectations. Objective This study aimed to examine in depth the disability status of individuals with chronic diseases and their expectations of disability services. Methods This qualitative study was conducted in Türkiye, and participant recruitment was carried out between 09/07/2024 and 07/01/2025. Semi-structured, in-depth interviews were conducted with 12 adults with chronic diseases who held official disability reports. Participants were recruited using purposive sampling combined with a snowball technique. Data were analyzed using inductive content analysis informed by a phenomenological perspective. Results Seventy percent of the participants were women, 50% had type 1 diabetes, and half reported limited awareness of disability services. Three main themes emerged: Impact of Disability on Daily Life, Awareness of Disability Services, and Accessibility of Disability Services. These findings highlight critical gaps between formal disability certification and effective access to services, indicating that informational and structural barriers persist despite legal entitlements. Conclusion Disability related to chronic illness affects multiple life domains, particularly social, cultural, educational, and professional areas. Although individuals with chronic diseases are entitled to disability services based on health board reports, limited awareness and accessibility hinder effective utilisation.